2022
DOI: 10.3390/ijms23147898
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Response to Cisplatin-Based Neoadjuvant Chemotherapy of Muscle-Invasive Bladder Cancer Patients by Molecular Subtyping including KRT and FGFR Target Gene Assessment

Abstract: Patients with muscle-invasive urothelial carcinoma achieving pathological complete response (pCR) upon neoadjuvant chemotherapy (NAC) have improved prognosis. Molecular subtypes of bladder cancer differ markedly regarding sensitivity to cisplatin-based chemotherapy and harbor FGFR treatment targets to various content. The objective of the present study was to evaluate whether preoperative assessment of molecular subtype as well as FGFR target gene expression is predictive for therapeutic outcome—rate of ypT0 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…KRT20 was enriched in cell cycle checkpoint (GO),G2/M transition of mitotic cell cycle,mitotic sister chromatid segregation ,nuclear division, Cell cycle, Spliceosome, Primary bile acid biosynthesis, DNA replication, Lysosome, etc. Some studies have con rmed that KRT20 can promote the progression and drug resistance of malignant tumors, and has a great correlation with the prognosis [35,36]. However, some studies have shown that KRT20 is closely related to the benign differentiation of colon cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…KRT20 was enriched in cell cycle checkpoint (GO),G2/M transition of mitotic cell cycle,mitotic sister chromatid segregation ,nuclear division, Cell cycle, Spliceosome, Primary bile acid biosynthesis, DNA replication, Lysosome, etc. Some studies have con rmed that KRT20 can promote the progression and drug resistance of malignant tumors, and has a great correlation with the prognosis [35,36]. However, some studies have shown that KRT20 is closely related to the benign differentiation of colon cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical trial NCT02792192 reported 3% complete response, 37% partial response and 39% stable disease (median progression-free survival of 5.5 months). Notably, FGFR2 and FGFR3 gene mutations are especially relevant; mutations FGFR2 N549H , FGFR3 Y373C;V555M , increase tumor immunity to FGFR-inhibitors [65,66].…”
Section: Intravesical Delivery Systemsmentioning
confidence: 99%